On the origin of controlled anisotropic growth of monodisperse gold nanobipyramids - Meena, Santosh Kumar; Lerouge, Frederic; Baldeck, Patrice; Andraud, Chantal; Garavelli, Marco; Parola, Stephane; Sulpizi, Marialore; Rivalta, Ivan (Nanoscale, 2021)
We elucidate the crucial role of the cetyl trimethylammonium bromide (CTAB) surfactant in the anisotropic growth mechanism of gold nano-bipyramids, nano-objects with remarkable optical properties and high tunability. Atomistic molecular dynamics simulations predict different surface coverages of the CTAB (positively charged) heads and their (bromide) counterions as function of the gold exposed surfaces. High concentration of CTAB surfactant promotes formation of gold nanograins in solution that work as precursors for the smooth anisotropic growth of more elongated nano-bipyramidal objects. Nanobipyramids feature higher index facets with respect to nanorods, allowing higher CTAB coverages that stabilize their formation and leading to narrower inter-micelles channels that smooth down their anisotropic growth. Absorption spectroscopy and scanning electron microscopy confirmed the formation of nanograins and demonstrated the importance of surfactant concentration on driving the growth towards nano-bipyramids rather than nanorods. The outcome explains the formation of the monodisperse bipyramidal nano-objects, the origin of their controlled shapes and sizes along with their remarkable stability.